Analysis of Macroeconomic Indicators and the Impact of Dow Jones on the Indonesia Composite Index - Amalia Hafsha Zulfana Phartu; Retno Indah Hernawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The Jakarta Composite Index (JCI), also known as the Indonesia Composite Index is a key indicator that reflects the performance of the Indonesian capital market and serves as a reference for assessing economic conditions and making investment decisions. This study aims to examine the influence of macroeconomic factors such as inflation, the rupiah exchange rate, and interest rates along with an external factor, the Dow Jones Index, on the JCI during the period 2020–2024. This research contributes by incorporating the DJIA as a proxy for global market effects on the JCI and by using the most recent and comprehensive dataset covering the pandemic and subsequent economic recovery. A quantitative approach was employed, using monthly time-series secondary data. The study applied saturated sampling, resulting in 60 observations. The data were obtained from official sources, namely the Indonesia Stock Exchange (IDX), Bank Indonesia (BI), the Central Statistics Agency (BPS), and Investing.com. Multiple linear regression was used as the analysis technique. The results show that inflation and the Dow Jones Index have a significant positive effect with the JCI, while the rupiah exchange rate has a significant negative effect. In contrast, interest rates do not show a significant effect on the JCI. These findings suggest that investors should consider inflation, the exchange rate, and global market movements (DJIA) when making investment decisions, while interest rates may play a less prominent role.